Opioid versus non-opioid postoperative pain management in otolaryngology - Allison Keane; Kayla Jardine; David Goldenberg; Sandeep Pradhan; Jay Zhu; Jobran Mansour; Hadas Knoller; Ron Eshel; Yoav P. Talmi; Sonia Vaida; Guy Slonimsky (BMC Anesthesiology, 2023)
Abstract Background The opioid epidemic in the United States has had devastating consequences, with many opioid-related deaths and a significant economic toll. Opioids have a significant role in postoperative pain management. Here we aim to analyze differences in postoperative opioid and non-opioid pain medications regimens following common otolaryngological surgeries between two large tertiary care medical centers: the Milton S. Hershey Medical Center, USA (HMC) and The Chaim Sheba Medical center, Israel (SMC). Methods A retrospective chart review of patients undergoing common otolaryngological procedures during the years 2017–2019 was conducted at two tertiary care centers, one in the U.S. and the other in Israel. Types and doses of postoperative pain medications ordered and administered during admission were analyzed. Average doses ordered and administered in 24 h were calculated. Opioid medications were converted to a standardized unit of morphine milliequivalents (MME). Chi-square test and Wilcoxon rank-sum test were used to compare the groups. Results The study included 204 patients (103 U.S., 101 Israel). Patient demographics were similar except for a longer length of stay in Israel (p < 0.01). In the U.S., 95% of patients were ordered opioids compared to 70% in Israel (P < 0.01). In the U.S., 68.9% of patients ordered opioids received the medications compared to 29.7% in Israel. The median opioid dose ordered in the U.S. was 45MME/24 h compared to 30MME/24 h in Israel (P < 0.01), while median dose received in the U.S. was 15MME/24 h compared to 3.8MME/24 h in Israel (P < 0.01). Opioid prescriptions at discharge were given to 92% of patients in the U.S. compared to 4% of patients in Israel (p < 0.01). A significantly higher number of patients in the U.S. were prescribed acetaminophen and ibuprofen (p < 0.0001). Dipyrone was prescribed to 78% of patients in Israel. Conclusions HMC demonstrated a significantly more permissive approach to both prescribing and consuming opioid medications for postoperative pain management than SMC for similar, common otolaryngological surgeries. Non-opioid alternatives and examining the cultural and medical practice-based differences contributing to the opioid epidemic should be discussed and reevaluated.